Using combined Avrami-Ozawa method to evaluate low-temperature reversible aging in asphalt binders. Issue 1 (2nd January 2020) - Qiu, Yanjun; Ding, Haibo; Rahman, Ali; Yang, Enhui
Abstract : This paper aims to reasonably evaluate the reversible aging resistance of asphalt binders and comprehend the effects of low-temperature gradually hardening on fundamental properties of asphalt binders. To do so, extended bending beam rheometer (ExBBR) test with prolonged different conditioning times were performed on different kinds of asphalt binders, and viscoelastic mechanics model (Burgers model) was employed for describing the rheological properties. The combined Avrami-Ozawa equation was applied to characterise the non-isothermal crystallization process of asphalt binders which have a significantly different degree of physical hardening. The results showed that stiffness or m -value obtained from extended BBR test with logarithmic conditioning time has high coefficient of determination. Predicted stiffness and m -value from proposed empirical formula can be used to estimate extended BBR low temperature limiting grade (LTPG) that could be applicable for quality control (QC) purposes in the future. Lastly, the combined Avrami-Ozawa method can be successfully used to describe the non-isothermal crystallization process of asphalt binders used in this study.